AUGMENTED REALITY (AR) FOR MARMA POINT SCANNING AND WEARABLE THERAPEUTIC PATCHES: A CONCEPTUAL STUDY - Sonali Sharma (International Educational Journal of Science and Engineering, 2025)
This paper presents a conceptual framework for integrating Augmented Reality (AR) technology with Ayurvedic marma point therapy using wearable patches. The proposed system enhances accuracy in identifying marma points, provides real-time guidance for therapeutic interventions, and supports a personalized approach to traditional medicine. Marma points are classified according to Angula Parman, facilitating precise localization. AR visualization allows practitioners and students to explore marma locations interactively, while algorithm-driven guidance ensures correct patch placement and treatment protocols. This innovative approach combines traditional knowledge with modern technology, promoting integrative healthcare, education, and practitioner skill development.